2017
DOI: 10.1142/s0218348x17400035
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Microstructural Correlation of Slag/Superplasticizer Cement Pastes by Heat and Impedance Methods via Fractal Analysis

Abstract: This paper presents a preliminary work to evaluate the influence of slag and superplasticizer on the early-age hydration of cement pastes by an innovative non-contact impedance measurement, heat evolution method, compressive strength and setting time tests. Besides, the cumulative pore volume obtained from modulus and phase of impedance in different hydration sections is taken to continuously correlate the cumulative heat releasing of cement pastes via the fractal § Corresponding author. This is an Open Access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…These results are in good agreement with previous findings 28,60 that the compressive strength of concrete increased linearly with the decrease in porosity. In fact, it is generally agreed that the mechanical property of concrete depends on the pore structures 26,27 . These close correlations could explain the different effects of fly ash and silica fume on the mechanical property of concrete.…”
Section: Mip Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in good agreement with previous findings 28,60 that the compressive strength of concrete increased linearly with the decrease in porosity. In fact, it is generally agreed that the mechanical property of concrete depends on the pore structures 26,27 . These close correlations could explain the different effects of fly ash and silica fume on the mechanical property of concrete.…”
Section: Mip Resultsmentioning
confidence: 99%
“…There is a consensus that the mechanical and durability properties of concrete are closely related with its pore structure such as the porosity and the pore size distribution [26][27][28] . It has been suggested that the pore structure of concrete presents fractal characteristics within certain scales 24,26,29,30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, concrete is a typical porous material and possesses obvious fractal characteristics in pore shape, pore area and pore volume [20][21][22] . According to the fractal theory, the fractal dimension is an important parameter to characterize the complexity and inhomogeneity of the pores in concrete [21][22][23][24][25] .…”
mentioning
confidence: 99%
“…The branching networks such as tree branches, leaf veins, blood vessels, bronchial tree etc abound in nature, and fractal theory has been used to characterize the topology and transport properties of natural and industrial branching networks. 8 Sheng et al 9 introduced a random fractal algorithm based on Lindenmayer system to generate fracture networks according to the micro-seismic data, and evaluate the effective stimulated reservoir volume in shale gas reservoirs. Lu et al 10 presented a fractal model for the net present value of multi-stage fractured horizontal wells in tight gas reservoir, where a fractal gas permeability model with slippage effect was employed to characterize the apparent permeability of reservoir stratum.…”
Section: Overview Of Work In This Thematic Issuementioning
confidence: 99%